Analyses of elastic limit heat loads in thick walled tubes subjected to periodic surface temperatures: analytical treatment (Archives of Mechanics - Test, 2018)
Analytical solutions are derived to analyze elastic limit heat loads in tubes subjected to periodic surface temperatures. The tube is initially at zero temperature and for the times greater than zero one of the surfaces of the cylinder is subject to a periodic boundary condition while the other surface is insulated. For the transient temperature distribution, the heat conduction equation is solved by using Duhamel’s theorem. The uncoupled theory of thermoelasticity is used as the cylinder is heated or cooled slowly. Tresca’s yield criterion is used to monitor the yielding of the tube. The generalized plane strain condition is assumed. It is observed that yielding always occurs at the surface subject to a periodic boundary condition. It is also observed that, depending on the material properties of the tube and the amplitude of the boundary condition, yielding commences with different stress states.